At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the derivative [tex]\( f'(x) \)[/tex] of the function [tex]\( f(x) = 7x^8 + 5x^6 - 3x^5 + 2x^4 - 1 \)[/tex], we need to apply the power rule of differentiation. The power rule states that if [tex]\( f(x) = x^n \)[/tex], then [tex]\( f'(x) = nx^{n-1} \)[/tex].
Let's differentiate each term of the polynomial function separately:
1. For the term [tex]\( 7x^8 \)[/tex]:
[tex]\[ \frac{d}{dx}(7x^8) = 7 \cdot 8 x^{8-1} = 56x^7 \][/tex]
2. For the term [tex]\( 5x^6 \)[/tex]:
[tex]\[ \frac{d}{dx}(5x^6) = 5 \cdot 6 x^{6-1} = 30x^5 \][/tex]
3. For the term [tex]\( -3x^5 \)[/tex]:
[tex]\[ \frac{d}{dx}(-3x^5) = -3 \cdot 5 x^{5-1} = -15x^4 \][/tex]
4. For the term [tex]\( 2x^4 \)[/tex]:
[tex]\[ \frac{d}{dx}(2x^4) = 2 \cdot 4 x^{4-1} = 8x^3 \][/tex]
5. For the constant term [tex]\( -1 \)[/tex]:
[tex]\[ \frac{d}{dx}(-1) = 0 \][/tex]
Now, we sum up all these derivatives to get [tex]\( f'(x) \)[/tex]:
[tex]\[ f'(x) = 56x^7 + 30x^5 - 15x^4 + 8x^3 \][/tex]
Therefore, the derivative of the function [tex]\( f(x) \)[/tex] is:
[tex]\[ f'(x) = 56x^7 + 30x^5 - 15x^4 + 8x^3 \][/tex]
Let's differentiate each term of the polynomial function separately:
1. For the term [tex]\( 7x^8 \)[/tex]:
[tex]\[ \frac{d}{dx}(7x^8) = 7 \cdot 8 x^{8-1} = 56x^7 \][/tex]
2. For the term [tex]\( 5x^6 \)[/tex]:
[tex]\[ \frac{d}{dx}(5x^6) = 5 \cdot 6 x^{6-1} = 30x^5 \][/tex]
3. For the term [tex]\( -3x^5 \)[/tex]:
[tex]\[ \frac{d}{dx}(-3x^5) = -3 \cdot 5 x^{5-1} = -15x^4 \][/tex]
4. For the term [tex]\( 2x^4 \)[/tex]:
[tex]\[ \frac{d}{dx}(2x^4) = 2 \cdot 4 x^{4-1} = 8x^3 \][/tex]
5. For the constant term [tex]\( -1 \)[/tex]:
[tex]\[ \frac{d}{dx}(-1) = 0 \][/tex]
Now, we sum up all these derivatives to get [tex]\( f'(x) \)[/tex]:
[tex]\[ f'(x) = 56x^7 + 30x^5 - 15x^4 + 8x^3 \][/tex]
Therefore, the derivative of the function [tex]\( f(x) \)[/tex] is:
[tex]\[ f'(x) = 56x^7 + 30x^5 - 15x^4 + 8x^3 \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.